The effects of exercise and diet on weight loss maintenance in overweight and obese adults: a systematic review - R Kouvelioti; G. Vagenas; S Langley-Evans (The Journal of Sport Medicine and Physical Fitness, 2014)
Overweight and obesity are widespread nutritional disorders. Their treatment aims at effective weight loss (WL) and weight loss maintenance (WLM). Previous systematic reviews show weight regain, after recommended exercise and diet combined. However, certain experimental and methodological inconsistencies in the original studies and in these reviews left space for a substantial revisit of this problem. This study aimed at systematically re-reviewing the effectiveness of exercise combined with diet on WLM in overweight and obese adults. Literature was searched through Embase and Sport Discus (up to 2008), and PubMed (Medline) and ISI Web of science (up to 2012). 14 randomized clinical trials (RCT) were retained, their quality was assessed by the Jadad scale, and detailed methodological and statistical characteristics were evaluated. Overall estimations showed a WL of 11.1 kg (about 13%) after an average of about 4 months from baseline, a WLM of 5.8 kg (about 52%) and a weight regain of 5.1 kg after an average period of about 21 months. WL was successful but almost half of it (about 48%) was regained, which agrees with previous findings. The Jadad score showed very good to excellent quality for all 14 studies. However, further assessment revealed serious weakness such as high average dropout (>20%), not estimating experimental power or not using a control group in more than half of the studies, possible lack of adherence and variability in demographic traits. Future studies may focus on improving these limitations for more accurate results in this crucial research field.